Metabolomics Fundamentals and Applications - Prasain, Jeevan K. (IntechOpen, 2016)
Metabolomics: Fundamentals and Applications authoritatively presents the basic principles and applications of metabolomics. Topics covered in this book range from the analysis of metabolites from different biological sources and their data processing and statistical analysis. This book serves as a basic guide for a wide range of audiences from less familiar with metabolomics techniques to more experienced researchers seeking to understand complex biological systems from the systems biology approach.